The lutheran influence on Kant’s depraved will - Auweele, Dennis vanden (International journal for philosophy of religion, 2013)
Contemporary Kant-scholarship has a tendency to allign Kant’s understanding of depravity closer to Erasmus than Luther in their famous debate on the freedom of the will (1520–1527). While, at face value, some paragraphs do warrant such a claim, I will argue that Kant’s understanding of the radical evil will draws closer to Luther than Erasmus in a number of elements. These elements are (1) the intervention of the Wille for progress towards the good, (2) a positive choice for evil, (3) the inscrutability of moral progress, (4) the rejection of prudence as a means for salvation and (5) the rejection of moral sentimentalism. I believe that Kant-scholarship mistakenly pegs Kant’s rational Enlightenment optimism for an existential optimism while Kant’s view of fallen nature draws closer to Lutheran than Erasmusian depravity. A tacit Lutheran influence pervades Kant’s moral philosophy which could explain the influence Kant’s has had on some more pessimistic 19th century philosophers such as Arthur Schopenhauer and Friedrich Nietzsche.